Exploiting the therapeutic potential of the PI3K-AKT-mTOR pathway in enriched populations of gynecologic malignancies. Issue 6 (November 2014) - Eskander, Ramez N; Tewari, Krishnansu S
<x xml:space="preserve">Abstract</x> Given the prevalence of phosphatase & tensin homolog mutations in histologic specimens harvested from patients with endometrial cancer, significant interest in systemic treatment with PI3K/Akt/mTOR inhibitors has emerged. Several Phase II trials have been completed studying mTOR inhibitors in advanced/recurrent endometrial cancer. The mTOR pathway also appears to be important in some cervical cancers. Finally, because clear cell carcinoma of the ovary and renal cell carcinoma have a shared histology, the potential for activity of mTOR inhibitors in clear cell cancer of the ovary is implicit. This article reviews the results of Phase II clinical trials of PI3K/Akt/mTOR pathway inhibitors in patients with endometrial cancer, and discusses the potential therapeutic landscape of mTOR inhibition in enriched populations in gynecologic cancers.